CO2 reforming of methane over Zr-promoted Ni/SBA-15 catalyst : effect of zirconium loading - Harrydass, Ellapan (2016)
In the present time, increased concerns on anthropogenic greenhouse gas emissions and abundance of natural gas resources have renewed interest in the CO2 (dry) reforming process as an alternative to steam reforming for synthesis gas production from natural gas. The catalytic performance of catalyst is considered the most crucial field of study in CO2 reforming of methane. Various researches were conducted in order to optimize the conversion and minimize the deactivation rate of catalyst. In this research, the effect of Zirconium promoter on the Ni/SBA-15 catalyst at normal reaction temperature of CO2 reforming of methane had been carried out using a continuous-flow fixed-bed quartz reactor. A series of Zirconium promoted Ni/SBA-15 catalyst with different Zirconium contents (1, 3, 5, 7 wt %) prepared using modified sol-gel method. In addition, the catalyst samples with different Zirconium loadings characterized using BET surface measurement, Fourier Transform Infrared Spectroscopy (FTIR), X-Ray Diffraction (XRD) and Thermal Gravimetric Analysis (TGA). The synthesized Zr/Ni/SBA-15 catalyst tested for CO2 reforming of methane. This reaction is considered to be a great alternative to produce synthesis gas since it utilizes two abundant greenhouse gases. CO2 reforming of methane yields low hydrogen to carbon monoxide (H2/CO) ratio, which is desirable for many industrial synthesis processes. On the other hand, Zirconium promoted Nickel species enhances the formation of active center for the reaction. As a result, the promoted catalyst with 1wt% of Zr perform with optimum catalytic activity and producing higher amount of H2 at reaction temperature of 800oC compared to others. Zirconium species is well dispersed and promote the Nickel to be confined to the pores of SBA-15. The wall of SBA-15 limited the sintering of the Ni components. Thus, the Nickel species not undergone sintering as it is well embedded to SBA-15 which can withstand higher temperature.